Valproic Acid, a Histone Deacetylase Inhibitor, in Combination with Paclitaxel for Anaplastic Thyroid Cancer: Results of a Multicenter Randomized Controlled Phase II/III Trial. (27th September 2016) - Catalano, Maria Graziella; Pugliese, Mariateresa; Gallo, Marco; Brignardello, Enrico; Milla, Paola; Orlandi, Fabio; Limone, Paolo Piero; Arvat, Emanuela; Boccuzzi, Giuseppe; Piovesan, Alessandro
Abstract : Anaplastic thyroid cancer (ATC) has a median survival less than 5 months and, to date, no effective therapy exists. Taxanes have recently been stated as the main drug treatment for ATC, and the histone deacetylase inhibitor valproic acid efficiently potentiates the effects of paclitaxel in vitro . Based on these data, this trial assessed the efficacy and safety of the combination of paclitaxel and valproic acid for the treatment of ATC. This was a randomized, controlled phase II/III trial, performed on 25 ATC patients across 5 centers in northwest Italy. The experimental arm received the combination of paclitaxel (80 mg/m 2 /weekly) and valproic acid (1, 000 mg/day); the control arm received paclitaxel alone. Overall survival and disease progression, evaluated in terms of progression-free survival, were the primary outcomes. The secondary outcome was the pharmacokinetics of paclitaxel. The coadministration of valproic acid did not influence the pharmacokinetics of paclitaxel. Neither median survival nor median time to progression was statistically different in the two arms. Median survival of operated-on patients was significantly better than that of patients who were not operated on. The present trial demonstrates that the addition of valproic acid to paclitaxel has no effect on overall survival and disease progression of ATC patients. This trial is registered with EudraCT 2008-005221-11 .